Spirituality and Work Engagement in Ministry at the Indonesian Baptist Church Immanuel Simolangit - Menisa Laia; Yunita Stella; Sri Binar (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2023)
Every church congregation is expected to have engagement in ministry. However, in reality, there are still many congregations that are not actively engaged. At Indonesian Baptist Church Immanuel Simolangit, Surabaya itself, some members are reluctant to participate in worship, resulting in a lack of engagement in ministry. This study aims to determine whether there is an influence of spirituality on work engagement in ministry at Indonesian Baptist Church Immanuel Simolangit. The method used is quantitative research. The results of this study indicate that there is an influence of spirituality on work engagement in ministry at Indonesian Baptist Church Immanuel Simolangit. The calculation of simple correlation between spirituality and work engagement in ministry found an R value of 0.810, which is positively correlated. This means that the strength of the relationship between spirituality and work engagement in ministry at Indonesian Baptist Church Immanuel Simolangit is 0.810, falling into the category of very high correlation.